2005
DOI: 10.1051/0004-6361:20035738
|View full text |Cite
|
Sign up to set email alerts
|

PAH emission variations within the resolved starbursts of NGC 253 and NGC 1808

Abstract: Abstract. In order to better characterise the usefulness of PAH emission as a tracer of star formation, we have undertaken a programme of 3 µm narrowband imaging of a sample of nearby template galaxies covering a wide range of metallicity, star formation activity, and nuclear activity. In the present paper we present first results of this programme: high spatial resolution images of PAH feature emission and the adjacent continuum emission from the central regions of the nearby starburst galaxies NGC 253 and NG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
50
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 69 publications
10
50
2
Order By: Relevance
“…The fact that the shell detected in the Spitzer observations is undetected in the current study is puzzling in light of our NGC 253 3.3 µm imaging results (Tacconi-Garman et al 2005). In that work we found the first evidence for PAH molecules in a starburst-driven galactic superwind.…”
Section: Inner Kiloparseccontrasting
confidence: 64%
See 1 more Smart Citation
“…The fact that the shell detected in the Spitzer observations is undetected in the current study is puzzling in light of our NGC 253 3.3 µm imaging results (Tacconi-Garman et al 2005). In that work we found the first evidence for PAH molecules in a starburst-driven galactic superwind.…”
Section: Inner Kiloparseccontrasting
confidence: 64%
“…High spatial resolution 3 µm imaging has A&A 551, A139 (2013) been obtained for the entire sample, and the results for two starburst galaxies, NGC 253 and NGC 1808, have been published in Tacconi-Garman et al (2005).…”
Section: Introductionmentioning
confidence: 99%
“…Of normal star forming galaxies or those of low SFR, NGC 5529 and NGC 5907 appear to be the only known examples, thus far (see Table 1). Tacconi-Garman et al (2005) have found a λ 3.3 µm PAH feature in the superwind of the starburst galaxy, NGC 253, with z extent <120 pc, and there is now a clear PAH signature in the halo and superwind of M 82 to a distance of 6 kpc from the plane of that galaxy (Engelbracht et al 2006). Its 8 µm emission, which has a strong PAH component, resembles the Hα emission of the superwind in M 82, indicating that PAHs can survive in such an energetic environment and providing another example of a galaxy in which PAHs correlate with Hα emission in the halo.…”
Section: Discussionmentioning
confidence: 99%
“…Cesarsky et al 1996;Tacconi-Garman et al 2005). In addition, on galactic scales, some of the PAH emission may originate from the diffuse interstellar medium rather than starforming regions, as argued by based on the modeling of the dust emission of SINGS galaxies.…”
Section: Molecular Emission-line Diagnosticsmentioning
confidence: 99%